A good war for economic growth? - Pernica, Bohuslav; Sixta, Jaroslav (My University, 2023)
With an implementation of the UN´s System of National Accounts 2008 (SNA 2008), an unusual impact of wars on economic growth emerged. The SNA 2008 enables nations to include depreciations of military hardware into their Gross Domestic Product (GDP) calculations. Economic growth can be furthered not only by making heavy military investments in force modernisation, but donations of weapons and ammunition can also be factored into a nation’s national accounts. This research note presents how the SNA has affected Czechia, a member of both the EU and NATO, and which is a small size country that since 2022 has donated an extraordinary volume of second-hand hardware to Ukraine, which has contributed to the economic growth of Ukraine.
Je válka dobrá pro ekonomický růst?
Keywords: System of National Accounts; depreciation; military aid; Národní účetnictví; odpis; vojenská pomoc